The political, cultural, and dynastic history of the Farnese family: between the end of the Western Schism and the outbreak of the Italian wars, 1417-1494 - Luiten, L (2020)
This thesis investigates the strategies for the extension and perpetuation of power employed by the Farnese in Quattrocento Italy. It argues the preconditions of their success lay in their internal organisation, active government of their patrimony, and in the adoption of solutions to overcome the perils of partible inheritance. It addresses the decisions that governed the creation of dynastic and pseudo-dynastic ties and, above all, how the Farnese strengthened and maintained their kinship network. This network provided the basis for interactions in the political sphere on a peninsular level and within the Papal States. The argument is forwarded that the Farnese were at the heart of developments which saw an increase in political connections established across state boundaries, forcing historians to rethink the current consensus on state formation in Italy. Of particular relevance were the Farnese’s ties to the Medici in Florence, ties that grew in importance as the century progressed. Within the Papal States, the Farnese followed a policy of support for pontifical power, a policy as much perceived as a political tradition inherited from their ancestors as a practical approach to finding a working relation with the newly-established papacy in Rome after the end of the Western Schism, suggesting that traditional notions of papal-noble antagonism need to be replaced by a model that stresses collaboration. Moreover, the Farnese were among the first to profit from the growth in number of curial offices as they increasingly focused their ambitions on placing sons in the Church, ultimately leading to Alessandro Farnese’s nomination as cardinal. Finally, the Farnese’s patronage on Isola Bisentina and the creation of a family mausoleum, Franciscan friary, and sacred landscape are revealing of mid-century developments in devotional practices and illuminate the Farnese’s self-perception as a dynasty rooted in space and time, and their fabrication of dynastic memory.